2017
DOI: 10.1016/j.bpj.2017.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Binding Mechanisms in Nuclear Hormone Receptors by Monte Carlo and X-ray-derived Motions

Abstract: In this study, we performed an extensive exploration of the ligand entry mechanism for members of the steroid nuclear hormone receptor family (androgen receptor, estrogen receptor α, glucocorticoid receptor, mineralocorticoid receptor, and progesterone receptor) and their endogenous ligands. The exploration revealed a shared entry path through the helix 3, 7, and 11 regions. Examination of the x-ray structures of the receptor-ligand complexes further showed two distinct folds of the helix 6-7 region, classifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 41 publications
0
44
0
Order By: Relevance
“…High B-factor values are typically observed in the ligand-binding pockets of nuclear receptors known to bind natural or endogenous ligands such as PPARγ (Nagy and Schwabe, 2004), which is supported by dynamic data derived from NMR and HDX-MS studies (Bruning et al, 2007;(Hughes et al, 2012;(Johnson et al, 2000). In the six Nurr1 LBD molecules within the crystallography asymmetric unit (Wang et al, 2003), higher than average B-factor values ( Figure 3A) are observed for residues comprising the putative ligand entry-exit surface formed at the base of LBD where helix 3 and 11 meet with the helix 6-7 loop, as well as the helix 2-3 loop (Edman et al, 2015; (Grebner et al, 2017). Unfortunately, structure factors were not deposited for the Nurr1 LBD crystal structure, which limits further interpretation of the electron density of this structure.…”
Section: Crystallography Likely Captured a Collapsed Pocketmentioning
confidence: 65%
See 2 more Smart Citations
“…High B-factor values are typically observed in the ligand-binding pockets of nuclear receptors known to bind natural or endogenous ligands such as PPARγ (Nagy and Schwabe, 2004), which is supported by dynamic data derived from NMR and HDX-MS studies (Bruning et al, 2007;(Hughes et al, 2012;(Johnson et al, 2000). In the six Nurr1 LBD molecules within the crystallography asymmetric unit (Wang et al, 2003), higher than average B-factor values ( Figure 3A) are observed for residues comprising the putative ligand entry-exit surface formed at the base of LBD where helix 3 and 11 meet with the helix 6-7 loop, as well as the helix 2-3 loop (Edman et al, 2015; (Grebner et al, 2017). Unfortunately, structure factors were not deposited for the Nurr1 LBD crystal structure, which limits further interpretation of the electron density of this structure.…”
Section: Crystallography Likely Captured a Collapsed Pocketmentioning
confidence: 65%
“…The conformation of the loop connecting helix 6 and 7 in the apo-Nurr1 LBD, which is tucked into the putative pocket in close proximity to helix 3, stands out among the other fatty acid-bound nuclear receptor LBD structures, which show an open conformation where the helix 6-7 loop is further away from helix 3. Notably, the helix 6-7 loop region is a critical structural mediator of the ligand entry-exit site within the nuclear receptor LBD (Edman et al, 2015;(Grebner et al, 2017). In our Nurr1 NMR studies, residues in and near the helix 6-7 loop show very broad NMR linewidths and elevated Rex values, indicating exchange between two or more conformations on the μs-ms timescale.…”
Section: The Putative Pocket Can Expand To a Conformation Similar To mentioning
confidence: 73%
See 1 more Smart Citation
“…By expanding the exploration to tens/hundreds of computing cores, we can perform full nonbiased explorations, mapping the entire receptor surface in search for binding sites, in a similar fashion to the pioneer studies of the Shaw group; Figure shows PELE's exploration of the Src kinase, reproducing the dynamic binding observed by the Shaw group with unbiased MD. Several systems have been modeled in this manner, including quite complex ones such as the small molecule and peptide binding to prolyl oligopeptidase (Kotev, Lecina, Tarragó, Giralt, & Guallar, ), the binding of a porphyrin ligand into Gun4 (Kopečná et al, ), mTOR (Espona‐Fiedler et al, ) and BCL‐2 apoptotic targets (Hosseini et al, ), the human phosphomannomutase2 receptor (Andreotti et al, ), and on diverse nuclear hormone receptors (NHRs) in collaboration with AstraZeneca (Edman et al, ; Grebner et al, ). In all of these systems, coupling ligand dynamics to backbone conformational changes was key for effective binding; constraining the alpha carbons to the apo structures, for example, resulted in unsuccessful searches.…”
Section: The Pele Tool For Flexible Protein–ligand Samplingmentioning
confidence: 99%
“…PELE 29 is an alternative method of exhaustive sampling that allows simulating the whole binding event. It has been used in a wide range of recognition problems such as the exploration of binding mechanisms for nuclear hormone receptor ligands, 30 the computational prediction of resistance to HIV-1 protease inhibitors 31 or pose prediction for low-molecular-weight fragments, 32 and has been tested as an induced-fit docking algorithm for prospective binding mode prediction on a variety of targets with remarkable results, both in academic and industrial settings. 33,34 In this paper, we systematically investigate the recognition properties of the α2δ-1 subunit.…”
Section: Introductionmentioning
confidence: 99%